2016
DOI: 10.5964/psyct.v9i2.198
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in depression symptoms: Findings from a population survey in Kosovo – A country in transition

Abstract: This paper focuses on gender differences in depression symptoms. It takes into consideration relevant contextual factors of a country in transition. This paper's analyzed data was extracted from European Social Survey, Sixth Round (ESS-6). ESS uses strict probability samples of the resident national population, aged 15 or older, and living in private households. Females reported a significantly higher mean depression on average (M = 8.14; SD = 3.88) compared to males (M = 7.56; SD = 3.86) at t(1247) = 2.604, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…At a clinical level, both men and women presented with a similar level of psychopathology as measured by the BPRS (average rating of about 50 in the BPRS in both groups) which, overall, could be interpreted as markedly ill (Leucht et al, 2005). However, when specific symptoms were analysed, it emerged that worse anxiety and depressive symptoms were reported in women than in men which corroborates previous findings from both clinical and general populations about higher affective symptoms in women (Arenliu et al, 2016;Riecher-Rössler et al, 2018;Seedat et al, 2009). Indeed, as subjective anxiety (as measured by the anxiety subscale from BSI) did not result significantly different between women and men we could argue that the difference emerged from the BPRS anxiety-depression subscale would be mainly driven by affective symptoms.…”
Section: Whole Samplesupporting
confidence: 85%
See 1 more Smart Citation
“…At a clinical level, both men and women presented with a similar level of psychopathology as measured by the BPRS (average rating of about 50 in the BPRS in both groups) which, overall, could be interpreted as markedly ill (Leucht et al, 2005). However, when specific symptoms were analysed, it emerged that worse anxiety and depressive symptoms were reported in women than in men which corroborates previous findings from both clinical and general populations about higher affective symptoms in women (Arenliu et al, 2016;Riecher-Rössler et al, 2018;Seedat et al, 2009). Indeed, as subjective anxiety (as measured by the anxiety subscale from BSI) did not result significantly different between women and men we could argue that the difference emerged from the BPRS anxiety-depression subscale would be mainly driven by affective symptoms.…”
Section: Whole Samplesupporting
confidence: 85%
“…The current study focuses on a sample of subjects with schizophrenia from Kosovo, a low-income country in Southeastern Europe. Although the country is going through a period of rapid socio-economic changes, its socio-economic status is still deeply affected by the aftermath of war, which is known to profoundly impact mental health (Arenliu et al, 2016;Priebe et al, 2010). Moreover, the presence of culturally imposed gender roles originating from a patriarchal view of life (Färnsveden et al, 2014) can differently affect the way men and women both express mental health problems and seek professional help and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research by Winstok and Straus (2014) confirmed a rather complicated association between depressive symptoms and IPV, and according to the authors, this relationship depends on gender differences on motivation and outcomes of IPV. Although there is a general lack of data about depression in Kosovo, existing evidence showed that women reported higher rates of depression compared with men, but no statistically significant differences were found between men and women (Arenliu, Kelmendi, & Berxulli, 2016). In this regard, it is important to mention that the rapid social and cultural change that Kosovo has experienced after the end of war, and these contextual aspects, characterized by transitional roles that men and women in Kosovo are going through, appear to produce adverse effects for men and women, and as such they affect the overall mental health of men and women in Kosovo.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only a few studies have been conducted on this issue worldwide and those that included the population of Kosovo, supported the relation between the COVID-19 pandemic and incidence of cognitive distortion (e. g., anxiety and depressive symptoms) among healthcare professionals 30 and students 31 . However, to the best of our knowledge, no study has investigated the effects of media/news exposure about COVID-19 on cognitive distortion and anxiety in Kosovo.…”
Section: Introductionmentioning
confidence: 89%